Effect of high vacuum heat treatment on microstructure and cyclic oxidation resistance of HVOF-CoNiCrAlY coatings. (January 2017) - Salehi Doolabi, D.; Rahimipour, M.R.; Alizadeh, M.; Pouladi, S.; Hadavi, S.M.M.; Vaezi, M.R.
Abstract: CoNiCrAlY coatings were deposited on IN-738 LC substrates using HVOF technique. The microstructure of these coatings is composed of a single γ phase. A two-step high vacuum heat treatment transformed the single γ phase into a two-phase γ+β microstructure. The result of cyclic oxidation test at 1100 °C on the coated samples indicated a higher oxidation resistance in as-sprayed coatings than heat-treated samples. At initial oxidation cycles of the as-sprayed coatings, fine grain size and high dislocation density of single γ phase could enhance the diffusion rate of aluminum into the surface and increase the probability of alumina formation as the first oxide layer. Whereas two-phase microstructure together with coarse grain size and low dislocation density of the heat-treated coatings reduced the aluminum diffusion rate and decreased the possibility of having a single layer of alumina. After 50 oxidation cycles, a single layer of alumina oxide formed on the as-sprayed coatings with a more uniform thickness compared to a dual-layer oxide of alumina and spinel on the heat-treated coatings. At 260th oxidation cycle, the growth of initiated cracks in previous cycles reached a critical stage which led to spallation of the oxide layer. Highlights: CoNiCrAlY coatings were deposited on IN-738 LC substrates using HVOF technique. Effect of heat treatment on cyclic oxidation resistance of coatings was studied. Single alumina oxide layer formed on as-sprayed coating in early oxidation stages. Dual alumina/spinel oxide formed on heat-treated coating in early oxidation stages. As-sprayed coating showed higher oxidation resistance than heat-treated coating.